2021
DOI: 10.3390/vetsci8020023
|View full text |Cite
|
Sign up to set email alerts
|

Diastolic and Systolic Longitudinal Myocardial Velocities of Healthy Racing Pigeons (Columba livia f. domestica) Measured by Tissue Doppler Imaging

Abstract: Tissue Doppler imaging (TDI) is a noninvasive sonographic method of acquiring and quantifying myocardial velocities. This technique is used in human and small animal medicine to diagnose cardiac diseases. Using this technique, we evaluated the longitudinal myocardial peak velocities of the interventricular septum, and the left and right ventricular free walls in the systole and diastole in 40 racing pigeons. The TDI examinations confirmed the movement of the heart base toward the apex in the systole and away f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…A similar effect of anesthesia on the systolic and diastolic myocardial velocities can also be seen in mammals [24] [31]. The general distribution of the myocardial velocities in the anesthetized heart corresponds to the conditions in the conscious pigeons [3]. In anesthetized pigeons, there is also a velocity gradient from the basal segments with the highest velocities to the apical segments with very low velocities.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…A similar effect of anesthesia on the systolic and diastolic myocardial velocities can also be seen in mammals [24] [31]. The general distribution of the myocardial velocities in the anesthetized heart corresponds to the conditions in the conscious pigeons [3]. In anesthetized pigeons, there is also a velocity gradient from the basal segments with the highest velocities to the apical segments with very low velocities.…”
Section: Discussionsupporting
confidence: 57%
“…In these conscious birds, there was no correlation between peak myocardial velocities and heart rate in the range of 130 to 274 bpm. It could be assumed that in a study with higher heart rates and more animals a correlation can be statistically shown [3]. In contrast, in anesthetized pigeons, there was a negative correlation between the heart rates (range 78 - 215 bpm) and systolic peak myocardial velocities (S' wave) of the left free wall, the septum, and, to a lesser extent, of the right free wall.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation